Jacobsen syndrome in a patient with combined immunodeficiency, thrombocytopenia, congenital heart disease and facial dysmorphism: a case report and review of literature - Özdemir, Öner; Dikici, Ümmügülsüm; Yarar, Murat Hakkı (Alergologia Polska - Polish Journal of Allergology, 2025)
Contiguous gene (deletion) syndrome caused by partial deletion of the long arm of chromosome 11 is called Jacobsen syndrome (JS). Jacobsen syndrome is one of the rare causes of syndromic immunodeficiency. The phenotype of this syndrome continues to be elucidated by case series. This syndrome is characterized by growth and psychomotor retardation, facial dysmorphism, multiple congenital abnormalities, and thrombocytopenia. We present a JS patient with human inborn error of immunity and multiple anomalies. A 2-year-old Syrian female patient from non-consanguineous family who had tetralogy of Fallot surgery when she was 4 months old. She has facial dysmorphism, congenital cardiac malformation, thrombocytopenia, and lymphopenia. Immunodeficiency was detected in the patient. Intravenous immunoglobulin replacement therapy was started. Genetic mutation analysis coincided with JS. Genetic mutations should be investigated in immunodeficiency patients with multiple anomalies. It should not be forgotten that in some cases, genetic mutation should be studied with an array of methods beyond karyotype analysis.